Filterability of Streptococcal L-Forms - Wyrick, Priscilla B. (1971)
The filterability of the broth-grown stable L-form derived from Streptococcus faecium F24 was tested by filtration under the influence of varying amounts of applied pressure. A decrease in the pore size of the filter resulted in a corresponding decrease in viable count, but no major effect was noted due to the different pressures applied. Serial filtration of a deoxyribonuclease-treated L-form culture in the mid-logarithmic phase of growth resulted in recovery of viable L-forms from the 0.45-μm filtrate but not from the 0.22-μm filtrate. It is possible that disruption of the L-form bodies with release of small viable elements had occurred. Protoplasts, diluted in an osmotic stabilizer, were filtered similarly; L-forms could be grown from the filtrate passing through the filters of 0.45 μm or greater. Filtration of the parent streptococci gave rise to streptococcal colonies from the 1.2-μm filtrate only.